2019
DOI: 10.1007/s42452-019-1244-3
|View full text |Cite
|
Sign up to set email alerts
|

The influence of magnetic field on the fluid flow in the entrance region of channels: analytical/numerical solution

Abstract: The present paper investigates the steady laminar development flow of a Newtonian incompressible electrically conducting fluid in a plane channel subjected to a uniform transverse external magnetic field. In order to solve the problem, the analytical integral momentum method and numerical finite volume method (FVM) are conducted. In integral momentum solution, the Pohlhausen's fourth-degree velocity profile is assumed. Applying the boundary conditions leads to the appearance of a new dimensionless parameter na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Although Coey and Hinds claimed that the EMF alone is much smaller than other forces acting in the electrochemical reaction (like diffusion and migration), they concluded that the effect of the Lorenz force imposed by the EMF should not be neglected in the event that it is combined with another convictive movement in the electrolyte 36 . Utilization of electromagnetic eld (EMF) in chemical reactions has been studied intensively [37][38][39] . The main investigation was directed toward plasma reactions and uid ow through pipes.…”
Section: Introductionmentioning
confidence: 99%
“…Although Coey and Hinds claimed that the EMF alone is much smaller than other forces acting in the electrochemical reaction (like diffusion and migration), they concluded that the effect of the Lorenz force imposed by the EMF should not be neglected in the event that it is combined with another convictive movement in the electrolyte 36 . Utilization of electromagnetic eld (EMF) in chemical reactions has been studied intensively [37][38][39] . The main investigation was directed toward plasma reactions and uid ow through pipes.…”
Section: Introductionmentioning
confidence: 99%
“…Effects of Newtonian heating on boundary layer flow of non-Newtonian MHD nanofluid was well discussed by [16] where spectral relaxation method was used. This area was also explored by [17].On thermal conductivity and radiation, [18][19][20] dealt with it conclusively. Then [21] extended their work on impacts of Newtonian heating, variable fluid properties, and Cattaneo-Christov model on MHD stagnation point flow of Walters'B fluid induced by stretching surface.…”
Section: Introductionmentioning
confidence: 99%
“…Due to numerous practical application, magnetohydrodynamic (MHD) fluid flow through channels have received considerable attention during these decades. 1–11 Practical applications include channels in reactors, MHD flow meters, MHD generators, metallurgy industry, reactor cooling systems, pumps power generation, petroleum production, the MHD blood flow simulation in vascular networks, etc. The interaction between the applied magnetic field and conducting fluid flow induces an electromotive force which alters the velocity field distribution.…”
Section: Introductionmentioning
confidence: 99%